2014
DOI: 10.1111/poms.12044
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Competitive Environment on Supply Chain Information Sharing and Performance: An Empirical Study in China

Abstract: Information sharing in supply chains has become an important topic over the past decade. This study uses data from 617 Chinese manufacturing firms to investigate the relationships among competitive environments, supply chain information sharing (SCIS), and supply chain performance. The results of structural equation modeling analysis show that (i) international competition is positively related to all three types of SCIS whereas local competition is not significantly related to any of the three types, (ii) int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
231
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 186 publications
(251 citation statements)
references
References 115 publications
(299 reference statements)
14
231
1
5
Order By: Relevance
“…The goal of EMI sharing with supply chain partners is to enhance the ability of firms to develop environmentally friendly and responsible products and processes. The value of sharing information for SCM has been recognized in the literature with such performance benefits as reduced cost, better responsiveness, and improved services (Huo et al, 2014). The literature has also identified the contingencies influencing the success of inter-organizational information implementation for supply chain management which include asymmetry, reciprocity, efficiency, stability, and legitimacy covering the partner firms (Humphreys et al, 2001).…”
Section: Emi Sharing With Suppliers and Performancementioning
confidence: 99%
“…The goal of EMI sharing with supply chain partners is to enhance the ability of firms to develop environmentally friendly and responsible products and processes. The value of sharing information for SCM has been recognized in the literature with such performance benefits as reduced cost, better responsiveness, and improved services (Huo et al, 2014). The literature has also identified the contingencies influencing the success of inter-organizational information implementation for supply chain management which include asymmetry, reciprocity, efficiency, stability, and legitimacy covering the partner firms (Humphreys et al, 2001).…”
Section: Emi Sharing With Suppliers and Performancementioning
confidence: 99%
“…Thus, we need to investigate their effects in detail. Although strategic alliance and information sharing are popular topics in the strategic management and IT [39] and supply chain integration literature [26], coordination, especially supply chain coordination, is less emphasized. In addition, coordination studies mainly focus on the individual effects of coordination on performance (e.g.…”
Section: Effects Of Supply Chain Coordination On Supply Chain Performmentioning
confidence: 99%
“…IS positively affects performance in many ways like enhanced service levels, customer responsiveness, decreased costs, and reduced levels of complexity (Flynn et al, 2010). Huo et al (2014) has studies IS with supplies, customers and internal in Chines manufacturing and revealed that all have positive effect on operational performance and internal IS also has a positive relationship with external IS. IS has a positive effect on operational performance but not significantly in manufacturing sector of Turkey (Sezen, 2008).…”
Section: Information Sharing (Is)mentioning
confidence: 99%